2021
DOI: 10.1136/bmjopen-2020-045324
|View full text |Cite
|
Sign up to set email alerts
|

Markers of gastrointestinal permeability and dysbiosis in premenopausal women with PCOS: a case–control study

Abstract: ObjectivesAltered intestinal permeability and gut barrier dysfunction have been suggested to play a role in the pathogenetic mechanism of polycystic ovary syndrome (PCOS), the most common endocrine and metabolic condition in reproductive-aged women. However, data on intestinal permeability and dysbiosis of the gut microbiota in PCOS is still limited, with conflicting results. To this end, the concentrations of gastrointestinal permeability and gut dysbiosis markers were analysed in women with PCOS.DesignCase–c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…Lingaiah et al [ 60 ] reported serum zonulin levels in 104 women from Finland diagnosed with PCOS as part of a longitudinal birth cohort study, compared with 203 BMI-matched non-PCOS controls. All women were aged 46 years at the time of the study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lingaiah et al [ 60 ] reported serum zonulin levels in 104 women from Finland diagnosed with PCOS as part of a longitudinal birth cohort study, compared with 203 BMI-matched non-PCOS controls. All women were aged 46 years at the time of the study.…”
Section: Resultsmentioning
confidence: 99%
“…The investigators reported comparable serum levels of zonulin in both the study and control populations (128.0±17.0 vs. 130.9±14.0 ng/mL, P =0.13) (ELISA Kit, Immundiagnostik AG). Serum zonulin levels were correlated with BMI, IR, and inflammatory markers [ 60 ]. The generalizability of the results of this study is limited by the methodology and similarity of the study and control groups.…”
Section: Resultsmentioning
confidence: 99%
“…40 However, in terms of premenopausal women with PCOS at 46 years old, there was no variation in the serum levels of indicators for gut dysbiosis and gastrointestinal permeability. 41…”
Section: Abnormal Structure Of Gut Microbiota In Polycystic Ovary Syn...mentioning
confidence: 99%
“…Moreover, obese adolescents with PCOS (age 12 to 20 years, BMI > 90th percentile) have a lower richness of Bacteroidaceae and Porphyromonadaceae and higher Streptococcaceae at the family level 40 . However, in terms of premenopausal women with PCOS at 46 years old, there was no variation in the serum levels of indicators for gut dysbiosis and gastrointestinal permeability 41 …”
Section: Gut Dysbiosis In Polycystic Ovary Syndromementioning
confidence: 99%
“…Moreno-Navarrete et al [20] unveiled an association of this biomarker with obesity and insulin resistance, revealing elevated levels in obese and prediabetic patients. However, a handful of studies have dissected this biomarker in PCOS women, with findings being inconclusive [21][22][23], thereby leaving the role of zonulin in PCOS pathogenesis unresolved.…”
Section: Introductionmentioning
confidence: 99%